Stakeholder‐driven management strategies for recovering large herbivores - Sophia Hibler; Christian Kiffner; Hannes J. König; Niels Blaum; Emu‐Felicitas Ostermann‐Miyashita (Conservation Science and Practice)
Abstract In modern landscapes, the sustainable coexistence of humans and wildlife depends on involving stakeholders in the development and implementation of management strategies. This is particularly important for species like the European bison (Bison bonasus) and Eurasian moose (Alces alces), which are reoccupying regions between Germany and Poland after a prolonged absence. The return of these species generates mixed emotions, as interactions with these species are associated with both costs and benefits to people. Addressing the apparent unpreparedness in managing these trade‐offs, we implemented a digital participatory impact assessment in two steps. First, we engaged bison and moose experts to develop management scenarios and assessment criteria. Then, in a subsequent virtual workshop, stakeholders evaluated four scenarios along economic, social, and ecological dimensions. Quantitative and qualitative analyses revealed divergent perspectives and priorities, yet consensus emerged on the necessary future steps: formulating a comprehensive management strategy with guidelines and protocols for managing specific conflict scenarios, such as the incursion of large herbivores onto highways. Our approach underscores the importance of early stakeholder engagement in fostering a more equitable and sustainable management of human‐wildlife interactions. Moreover, demonstrating the feasibility of remote stakeholder involvement, our study presents a robust model for enhancing coexistence, adaptable even where in‐person meetings are challenging.